COMPOUND WORDS IN THE FILM DUNE BY DENIS VILLENEUVE (A MORPHOLOGICAL ANALYSIS) - Gloria Kemby; Donald R. Lotulung; F. Ari Anggriani Sebayang (Universitas Sam Ratulangi, 2025)
This study is titled “Compound Words in the Film Dune (A Morphological Analysis).” The primary objective of this study is to identify, categorize, and analyze the meanings of compound words found within the film’s dialogue. The analysis is grounded in morphological theories, particularly those proposed by McCarthy (2002) and Nida (1949), which serve as the main theoretical framework for identifying and interpreting the data. This research adopts a qualitative descriptive approach to provide a detailed examination of how compound words function in the context of the film. The result of this study revealed that there are 50 compound words, distributed as 30 compound nouns, 1 compound verb, 6 compound adjectives, 5 compound adverb, and 8 compound pronouns. Four formation patterns were observed in compound nouns—Noun + Noun, Verb + Noun, Adjective + Noun, and Preposition + Noun. One compound verb with Verb + Noun pattern. Four patterns underlie compound adjectives—Noun + Adjective, Verb + Adjective, and Adjective + Adjective and Adjective + Noun—and one compound adverb are formed by Preposition + Noun. In addition, there are 30 endocentric and 20 exocentric compound words found in this research.